Effect of age on the grading of carcass of indigenous cattle in Bangladesh - Islam, MS; Hossain, MM; Akhter, S; Noman, MA Al; Goswami, PK; Hashem, MA (Meat Research, 2022)
The objective of this study was to examine the effect of age on the grading of carcass of indigenous cattle. This experiment was conducted with five (5) treatments (T1 , T2 , T3 , T4 and T5 ) where T1 = 0 Permanent incisor, T2 = 2 Permanent incisors, T3 = 4 Permanent incisors, T4 = 6 Permanent incisors, T5 = 8 Permanent incisors having ten (10) replications. From this study, the mean rib eye muscle area (REA) and the mean rib fat thickness was 43.26, 49.93, 61.38, 70.43, 69.24 cm2 and 0.61, 0.68, 0.66, 1.07 and 0.97 cm with T1 , T2 , T3, T4 and T5 , respectively. The mean retail cut percentage of our indigenous beef cattle was 52.36, 52.27, 53.32, 52.69 and 52.58 with T1 , T2 , T3, T4 and T5 dental age groups, respectively. It also reveals that the overall maturity (on the basis of skeletal maturity and lean maturity) of indigenous beef cattle was A80 , B 90 , C 90, D80 and E 80 withT1 , T2 , T3, T4 and T5 dental age groups, respectively. Indigenous cattle population was fallen in the marbling sub groups of Slight91 , Small90, Small59, Modest57 and Moderate40 with T1 , T2 , T3, T4 and T5 dental age groups, respectively. With the combination of overall maturity and marbling score, indigenous cattle for beef production possess in the quality grade of Select, Choice, Commercial, Utility and Utility with respect to T1 , T2 , T3, T4 and T5 dental age groups. Indigenous cattle did not satisfy the criteria for the highest quality grade e.g., Prime to Standard and the lowest quality grade e.g. Cutter to Canner. In conclusion, dental age maturity had a highly significant (p<0.001) effect on average skeletal maturity, marbling score of the carcass and also had a significant (p<0.01) effect on rib fat thickness as well as on rib eye muscle area (REA) irrespective of all age group of indigenous beef carcass in Bangladesh. This research will play a vital role in the path toward the development of Bangladeshi beef standards and will be helpful to grade indigenous beef cattle at butcher or commercial beef industries level.